2010
DOI: 10.1016/j.neuropsychologia.2010.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Detestable or marvelous? Neuroanatomical correlates of character judgments

Abstract: As we learn new information about the social and moral behaviors of other people, we form and update character judgments of them, and this can profoundly influence how we regard and act towards others. In the study reported here, we capitalized on two interesting neurological patient populations where this process of complex "moral updating" may go awry: patients with bilateral damage to ventromedial prefrontal cortex (vmPFC) and patients with bilateral damage to hippocampus (HC). We predicted that vmPFC patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 44 publications
3
55
0
Order By: Relevance
“…They subsequently proposed that the main function of EAM may in fact be a social one. The possible contribution of EAM to social regulation was also implied by a recent study that showed that severe EAM deficits interfere with the updating of moral character judgments of others and consequently may influence the way we perceive and behave towards others (Croft et al, 2010).…”
Section: Memory Development and The Development Of A Selfmentioning
confidence: 94%
“…They subsequently proposed that the main function of EAM may in fact be a social one. The possible contribution of EAM to social regulation was also implied by a recent study that showed that severe EAM deficits interfere with the updating of moral character judgments of others and consequently may influence the way we perceive and behave towards others (Croft et al, 2010).…”
Section: Memory Development and The Development Of A Selfmentioning
confidence: 94%
“…In humans, the ventromedial prefrontal cortex, including the subgenual (subcallosal) anterior cingulate cortex (Brodmann's area 25), plays a role in attributing emotional salience to newly acquired social information (Croft et al, 2010). Uncertain threatening situations that demand a global response (rather than precise action) activate the ventromedial prefrontal cortex in humans, too.…”
Section: Ventromedial Prefrontal Cortex Encodes Emotional Behaviormentioning
confidence: 99%
“…In this vein, difficulties with recollecting emotional events and/or autonoetic consciousness were propounded to exist in offenders with psychopathy, who feature impairments in empathy and affective ToM (Shamay-Tsoory and Aharon-Peretz, Craig et al, 2009). Croft et al's (2010) results suggested that severe EAM impairments due to neurological incidents may affect the updating of moral character judgments and subsequently may influence the way these individuals perceive and behave toward others. The authors compared in their study the performance of patients with bilateral damage to the ventromedial prefrontal cortex to that of patients with bilateral damage to the hippocampal formation (due to hypoxia/anoxia or herpes viral encephalitis) and that of a control brain-damaged group during a task that required the participants to make moral judgments about unfamiliar persons in two conditions (before and after being exposed to various social context scenarios).…”
Section: Introductionmentioning
confidence: 96%